Tantangan Dan Peluang UMKM Dalam Menghadapi Transformasi Digital (Studi Kasus : Kota Pamekasan) - Fadali Rahman; Ach. Areadi; Asroful Anam; Enggar Rifaldi; Mohammad Faris (PT. Hasba Edukasi Mandiri, 2025)
Digital transformation has become a significant phenomenon in the development of the national economy, including for Micro, Small, and Medium Enterprises (MSMEs). This study aims to identify the challenges and opportunities faced by MSMEs in Pamekasan City in the process of adopting digital technology. The research method employed is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving 10 MSME actors from various business sectors. The findings indicate that the main challenges faced by MSMEs include limited digital literacy, lack of capital for technology investment, and resistance to change. On the other hand, opportunities arise from increased access to digital markets, operational efficiency, and collaboration with e-commerce platforms. This study emphasizes the importance of training support and local government policies to accelerate the digital transformation of MSMEs in Pamekasan.